Методичний підхід до прогнозування та оцінки потенціалу розвитку кіберспорту - Чизмар Іван; Csizmár Iván; Chyzmar Ivan (ТОВ «ДКС Центр», 2021)
У статті висвітлено особливості формування комплексного методичного підходу до прогнозування та оцінки потенціалу розвитку кіберспорту. При цьому окреслений підхід до прогнозування та оцінки сформований відповідно до особливостей його орієнтації на динамічне програмування, якому властива наявність таких рис: керованість процесів; багатокроковість; структурованість, змістовна деталізація. Зокрема, у межах дослідження реалізовані системний опис складових потенціалу розвитку кіберспорту, опис підходів до прогнозування та оцінки складових потенціалу розвитку кіберспорту та формування комплексного методичного підходу до прогнозування та оцінки потенціалу розвитку кіберспорту. Застосований автором метод дослідження узагальнює такі засоби, як логічний аналіз складових потенціалу розвитку кіберспорту, їх систематизацію та коригування нових і отриманих раніше знань. Відповідно до систематизованої сукупності кроків до прогнозування та оцінки потенціалу розвитку кіберспорту такі процеси мають реалізуватися через різні підходи до конкретизації багатокрокових задач оптимального управління комплексами взаємопов'язаних ресурсів (інтерфейсних, техніко-економічного розвитку, розширення виробництва). Важливо зазначити, що відмічена важливість конкретизації здатностей використання комплексів взаємопов'язаних ресурсів для підвищення спроможностей кіберспортивних організацій до їх еволюціонування. Відмічена важливість врахування керованості підвищення спроможностей, а не природної течії цього процесу. Для цього серед множини усіх припустимих управлінь відшуковують оптимальну (у сенсі критерію, який призводить до найбільшого і найменшого значення цільової функції). Подальшими перспективами дослідження є виокремлення основних рис, логіки та основи моделювання процесів розвитку кіберспорту як нової сфери цифрової економіки.

In the field of cybersport, there are problems in defining: the methods for identifying the state of the production and economic activities of cyber-sporting organizations; the logic of selecting adequate methods to identify the state of the production and economic processes of cybersports organizations within the target formal groups of the publisher/developer of the cybersports game; the directions of identification methods for determining the kinship of production and economic activity processes are determined by the potential of cybersport development. The article highlights the features of the formation of a comprehensive, methodical approach to forecasting and evaluating the potential of cybersport development. At the same time, the outlined approach is formed in accordance with the characteristics of its orientation to dynamic programming, which has such features as manageability of processes; multistep; structuring; meaningful detail. In particular, the study contains a systematic description of the components of the potential for developing cybersports, a description of approaches to forecasting and assessing the potential of cybersport development, and the formation of a comprehensive methodological approach to forecasting and evaluating the potential of cybersport development. The research method applied by the author contains such means as logical analysis of the components of the potential of cybersport development, their systematization and correction, new and received knowledge. According to the systematic set of steps for forecasting and evaluating the potential of developing cybersport, such processes must be implemented through various approaches to concretizing the multi-step tasks of optimizing the management of interconnected resource complexes (interfaces, techno-economic development, and expansion of production). The importance of specifying the capabilities of interconnected resource sets in order to enhance the ability of cybersports organizations to evolve was noted. The importance of taking management into account increases opportunities rather than the natural course of the process was noted. Further research perspectives highlight the main features, logic, and basis of modeling the development of cybersport as a new area of the digital economy.
Methodological approach to forecasting and assessment of development potential of kibersportu
Редакційна колегія: https://www.nayka.com.ua/index.php/investplan/about/editorialTeam
Зміст: http://www.investplan.com.ua/?n=18&y=2021
Keywords: кіберспорт; прогнозування; оцінка; виробничо-господарська діяльність; кіберспортивні організації; cybersport; forecasting; evaluation; production and business activities; cybersports organizations